Potensi sumber daya geologi di daerah Cekungan Bandung dan sekitarnya - Sutikno Bronto; Udi Hartono (Indonesian Journal on Geoscience, 2006)
DOI: 10.17014/ijog.vol1no1.20062aGeologically, Bandung Basin and the surrounding area comprise volcanic rocks; therefore, originally the geological resources, such as energy, environmental geology and mineral were generated from past volcanic activities. Energy resources having been utilized or in the exploration stage are water energy (Saguling Electrical Hydro Power) and geothermal energy (Darajat, Kamojang, Wayang-Windu and Patuha Geothermal Fields). Potency of hydrocarbon energy is considered due to the presence of Tertiary sedimentary rocks under Bandung volcanic rocks. Environmental resources include water, soil, land, and natural panorama that mostly are already used for living, tourism, industry etc. Mineral resources cover metals and non metals. Mineral explorations, particularly for gold, have been conducted in the southern Bandung area. Recently, Center for Geological Survey itself has found a new mineral resource in the northern Bandung, i.e. Cupunagara Village, Cisalak Sub-Regency, Subang Regency - West Jawa.